Implementing business related projects in Foundation Commerce: Business studies units - Law, Wendy Li Ling; Giridharan, Beena; Lau, Crystal Chun Yun; Lee, Che Siong; Quifors, S. (Enhancing Learning: Teaching and Learning Conference 2011 , Curtin University Sarawak, 2011)
Group-based class projects have been used as popular pedagogical tools by many institutions in developing team-work skills among students. The ability to work in teams is a much valued skill sought by many organisations (Shaw, 2004). Studies on the inclusion of business related group projects as assessments at foundation programs level, is scarce. This paper reports on a case study that investigated the perceptions of both students and staff regarding the inclusion of business related group projects in commerce units in a foundation programme. The study looked at students’ learning experiences, knowledge gained, and attitudes towards group-based assessments reflecting the effectiveness and value of including group projects in commerce units. The units which incorporated group based projects include Accounting, Business Management and Economics. In general, students agree that group-based projects facilitate learning new skills or concepts from team members, enhance problem solving skills, and promote team work skills. The teaching staff’s perceptions on the inclusion of the projects were encouraging and positive for most units. However, the implementation process of the projects for some units, warrant further investigation in order to enhance and improve the learning experiences of the students.